1997
DOI: 10.1021/bi971598z
|View full text |Cite
|
Sign up to set email alerts
|

The Orphan Nuclear Receptor TR2 Suppresses a DR4 Hormone Response Element of the Mouse CRABP-I Gene Promoter

Abstract: The mouse orphan nuclear receptor TR2-11-f suppressed the expression of reporters fused to a hormone response element of the mouse cellular retinoic acid-binding protein I gene promoter. TR2-11-f was able to bind to a direct repeat with four nucleotides in the spacer (5'TGACCTTTGGGGACCT3') located within this hormone response element as homodimers. The specificity of protein-DNA interactions was demonstrated by competition in gel retardation and antibody-mediated supershift reactions. The residues critical for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
28
0

Year Published

1998
1998
2009
2009

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 32 publications
1
28
0
Order By: Relevance
“…Like many other orphan nuclear receptors, the activities of TR2 have been demonstrated to be primarily repressive in many systems without putative ligands (14,15,19). Many genes that are demonstrated to contain a DNA response element for TR2 are involved in RA metabolism, such as cellular retinoic acid-binding protein I and cellular retinol-binding protein II.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Like many other orphan nuclear receptors, the activities of TR2 have been demonstrated to be primarily repressive in many systems without putative ligands (14,15,19). Many genes that are demonstrated to contain a DNA response element for TR2 are involved in RA metabolism, such as cellular retinoic acid-binding protein I and cellular retinol-binding protein II.…”
Section: Discussionmentioning
confidence: 99%
“…A fragment containing only the DR5 (16) was also prepared by annealing oligonucleotides spanning DR5 site and used as a control for TR2 binding. ␤2 by TR2 Expression-Previously, the biological activity of orphan receptor TR2 was demonstrated to be primarily suppressive on both RA induction of DR5-containing reporters (16,17) and reporters regulated by some hormone response elements such as DR4 (14) and DR1 (15). It was demonstrated that the suppressive activity required the intact LBD and DBD but not the N-terminal A/B domains of the molecule (16).…”
Section: Tr2 As a Constitutive Activator For Rar␤2mentioning
confidence: 99%
See 1 more Smart Citation
“…By using a retinoic acid (RA)-responsive reporter that contains a direct repeat (DR)-5 (DR5) type RA response element (RARE) of the retinoic acid receptor (RAR ) gene (Sucov et al 1990), we have demonstrated that TR2, but not TR2-11-t, repressed RA induction of this reporter in a dose-dependent manner (Lee et al 1996a. By using a reporter containing a DR4-type hormone response element of the mouse cellular retinoic acid binding protein I (CRABP-I) gene, we have also shown that TR2, but not TR2-11-t, strongly repressed this reporter (Chinpaisal et al 1997). In other promoter systems such as the Simian virus (SV) 40 promoter (Lee & Chang 1995) and the erythropoietin gene promoter (Lee et al 1996b), TR2 also functions primarily as a transcriptional repressor (Lin et al 1995).…”
Section: Introductionmentioning
confidence: 91%
“…The mammalian forms of TR2 are expressed at a high level in adult testis and particularly in the postmeiotic germ cells (11)(12)(13)(14). Previous studies have demonstrated that TR2 is a potent repressor of retinoic acid (RA), thyroid hormone (T3) and vitamin D3 mediated transcriptional activity of their cognate receptors via competitive binding to the hormone response elements of DR series (18)(19)(20)(21)(22)(23)(24)(25). However, a recent report also demonstrated a role of TR2 as an activator of RAR2 gene promoter where TR2 in association with CREM activates the gene (26).…”
Section: Introductionmentioning
confidence: 99%